“Crying and Chaos” – Starting School Experiences of Teachers in the United Arab Emirates (UAE) - Takriti, Rachel; Atkinson, Susan; Rickett, Bridgette; Mohamad, Fatme; Al Dhaheri, Mouza (International Journal of Educational and Life Transitions, 2022)
The transition to full time schooling can be considered as the most important academic move that children make. Cross-cultural research demonstrates that a positive start to school leads to a more successful school career, academically and socially. Therefore, understanding the viewpoints of teachers about the first days in school is essential in understanding what contributes to a successful transition. This study focused on teacher experiences and perspectives of children starting school in the private school system in the United Arab Emirates (UAE). Ten teachers were interviewed using semi structured interviews. Thematic analysis revealed two themes: ‘A New Order’ and ‘Talking not Crying’, along with associated sub-themes. The findings indicated that the focus of the first few days at school was on establishing routines and order, which would indicate successful transition. Crying rather than talking is seen as a barrier to the establishment of the new order and, therefore, is seen as a hindrance to a successful transition. Consideration of cultural factors in how teachers view transition is given with suggestions for best practice in the context, specifically in relation to transition preparation and how to target hard to reach groups. Areas of focus and directions for future research are highlighted.
Keywords: Starting School; UAE; Teachers; Thematic Analysis; Interviews